Physicochemical properties of surimi made from edible insects using washing and pH shift methods - Chae-Ryun Moon; Young-Woong Ju; Su-Hyeon Pyo; So-Won Park; Seul Lee; Mzia Benashvili; Yang-Ju Son (Current Research in Food Science)
Edible insects, characterized by their eco-friendly nature and high nutrient value, are promising protein sources. Therefore, we aimed to assess the suitability of insects as source ingredients for surimi, a widely-used, intermediate food material. Mealworm (Tenebrio molitor L.) and two-spotted cricket (Gryllus bimaculatus L.) surimi were prepared, and their physicochemical and rheological properties were examined. Myofibrillar protein-rich fractions were obtained using the washing and pH shift methods. For the pH shift method, the myofibrillar proteins were extracted at acid (pH 2) or alkaline (pH 11) conditions, and surimi gel was prepared by heating myofibrillar protein-rich fractions. The pH shift method resulted in a higher surimi yield from edible insects than the washing method, whereas the washing method resulted in a higher surimi yield from tilapia (Oreochromis niloticus) and chicken breast (Gallus gallus domesticus). After acid treatment, lipid oxidation increased in all samples; however, edible insect surimi exhibited lower oxidation levels than tilapia and chicken breast surimi. Insect proteins, except for acid-treated mealworm proteins, successfully formed gel structures upon heating, resulting in softer gels than those obtained from tilapia and chicken breast. Consequently, the pH shift method resulted in elevated insect surimi yield, and the alkaline treatment was more appropriate for producing fine-quality edible insect surimi. Our study demonstrates the usefulness of edible insects as surimi ingredients, particularly for soft-gel food production. These findings emphasize the innovative application of edible insects in the food industry, suggesting the possibility of expanding their use as alternative protein food ingredients.